Manajemen Berbasis Cipta, Rasa, dan Karsa dalam Membangun Budaya Etika Pengelolaan Sampah: Studi Kasus Kota Bandung - Wati Rahayu; Hari Imbrani; Abdul Patah (Lembaga Pengembangan Kinerja Dosen, 2025)
Waste management in urban areas, especially in the city of Bandung, faces complex challenges that require strategies based on local values. This study examines how the concepts of Cipta, Rasa, and Karsa can be integrated into managerial practices in order to strengthen the ethical culture of waste management. Using a qualitative approach and case study design, data was obtained through a literature study by collecting, studying and reviewing various scientific literature and documents to find relevant information and then conduct field observations, as well as documentation of community and local government activities involved in waste management. The findings show that the application of the values of Cipta (creative ideas), Rasa (social care and empathy), and Karsa (initiative to act) can form responsible and ethical collective behavior in managing the environment. This approach encourages the emergence of community-based leadership and synergy between the community and government apparatus, which has an impact on increasing citizen awareness and participation. This study recommends the importance of integrating local values in public management systems, especially in dealing with urban environmental issues. In addition to making practical contributions, this research also makes a theoretical contribution to the development of a management model based on local cultural wisdom in Indonesia.